CANDIDA ALBICANS’IN TAKSONOMİSİNDEKİ ÖNEMLİ BAZI DEĞİŞİKLİKLER - YÜCEL, Ayhan; KANTARCIOĞLU, A. Serda (Cerrahpaşa Medical Journal, 2014)
Background.- The genus Candida is classified in the family Cryptococcaceae and included about 200 species in recent taxonomic treatise. C. albicans is the more frequent pathogenic species and is also part of normal human flora. Recently, germ tube and chlamydospore positive Candida albicans strains with abnormal characteristics have been isolated from primarily oral candidiasis in HIV infected (HIV+) individuals and AIDS patients. This isolates have very close phenothypic properties to those of C. albicans but a distinctive atypical genomic organisation. First identified as a new species of Candida in Ireland in 1995 and the name Candida dubliniensis has been proposed. C. stellatoidea, C. claussenii and C. langeronii has been reduced to synonymy of C. albicans on the basis of their significant DNA relatedness.